Experimental aspects of diagnostic and treatment methods applied for productive animal husbandry in Dnipro area (Ukraine) - Vakulik, Vyacheslav; Vakulyk, V. V.; Vakulik, V. V.; Vakulyk, Viacheslav; Vakulyk, V.; Vakulyk, Vyacheslav Volodymyrovich; Вакулик, Вячеслав Володимирович; Sklyarov, Pavlo; Sklyarov, Pavel; Sklyarov, P. M.; Skliarov, P. M.; Sklyarov, P.; et al. (Дніпровський ДАЕУ, 2025)
The publication explores the historical development of diagnostic, therapeutic, and experimental methods applied to non-contagious diseases within the zemstvo veterinary practice of Dnipro Ukraine. It traces the evolution of approaches, the adaptation of general biological and medical achievements, and the mutual influences between Ukrainian veterinary medicine and global scientific practice. Particular attention is given to the advancement of surgical techniques, anesthesiology, reproductive medicine, the design of surgical equipment, and therapeutic treatments. The work highlights the contributions of Mykhailo Maltsev, Moysey Koyranskyi, Mykola Shadrin, Serhii Yevseienko, Serhii Hrintser, Yevdokym Telychenko, and A. Popov. The impact of folk medicine and local veterinary culture on disease prevention and control is assessed. The study characterizes the patterns of veterinary progress, driven primarily by the zemstvo service. It demonstrates the dynamic integration of scientific developments into practice and the reciprocal influence of field experience on academic research. Following the elimination of major epizootic threats, a full-scale development of methods for managing non-contagious pathology began. The invention of an operating table for large animals by Moysey Koiranskyi serves as an example of professional competition and the complex journey from workshop innovation to industrial implementation. The publication conveys the “spirit of the era,” comparing professional relationships of the late 19th – early 20th centuries with those of today. It acknowledges that the period under study coincides with the rule of the Russian Empire, when Ukrainian specialists lacked the opportunity to publish in their native language or establish independent veterinary institutions. Nonetheless, the role of periodicals as platforms for collegial exchange, experience sharing, and scientific discourse is emphasized. Zemstvo veterinary community has served as both the analysts and the expert cohort while their research aimed to solve practical aspects. They did not reject folk medicine, often turning to medicinal plants due to limited access to pharmaceuticals. This reveals a deep connection between veterinary practice and the everyday life of the population, forming a distinct national character and tradition within regional veterinary culture. The development of obstetrics, gynecology, surgery, and andrology, as well as the establishment of breeding centers and agricultural exhibitions in Southeastern Ukraine, had both local and international significance. У статті досліджена історія розвитку методів діагностики та лікування незаразних захворювань у земській ветеринарній практиці Подніпрянської України. Простежено еволюцію підходів, адаптацію загальнобіологічних і медичних досягнень, а також взаємовпливи української ветеринарії зі світовою наукою. Особливу увагу приділено розвитку хірургічної практики, анестезіології, репродуктології, конструюванню операційного обладнання, терапевтичним методам. Наведено приклади діяльності Михайла Мальцева, Мойсея Койранського, Миколи Шадріна, Сергія Євсеєнка, Сергія Грінцера, Євдокима Теличенка А. Попова. Оцінено вплив народної медицини та ветеринарної культури населення на профілактику і ліквідацію захворювань тварин. Охарактеризовано закономірності ветеринарного прогресу, рушієм якого стала земська служба. Показано динаміку впровадження наукових розробок у практику та зворотний вплив практики на науку. Після ліквідації епізоотичних загроз розпочався повноцінний розвиток методів боротьби з незаразною патологією. На прикладі винаходу операційного столу Мойсея Койранського висвітлено професійну конкуренцію та шлях інновації – від майстерні фахівця до виробництва. Представлене дослідження передає «настрій часу», порівнює характер професійних відносин кінця XIX – початку XX століття із сучасністю. Враховано, що досліджуваний період припадає на часи Російської імперії, коли українські фахівці не мали змоги друкуватися рідною мовою чи створювати власні видання. Водночас підкреслено роль періодики як простору для обміну досвідом і наукових дискусій. Земські лікарі виступали аналітиками й експертами, їхні дослідження були спрямовані на вирішення практичних завдань. Вони не відкидали народну медицину, зверталися до лікарських рослин через нестачу препаратів. Це засвідчує глибокий зв’язок ветеринарії з народним життям і формування національного характеру ветеринарної культури. Розвиток акушерства, гінекології, хірургії, андрології, племінних центрів і виставок у Південно-Східній Україні мав як місцеве, так і міжнародне значення.
Експериментальні аспекти застосування методів діагностики та лікування продуктивних тварин у земських губерніях Подніпрянської України
Вакулик Вячеслав Володимирович https://orcid.org/0000-0001-8773-2287 Скляров Павло Миколайович https://orcid.org/0000-0002-4379-9583 Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384 Самойлюк Вячеслав Володимирович https://orcid.org/0000-0001-8400-8904 Масліков Сергій Миколайович https://orcid.org/0000-0003-1353-3968 Cуслова Наталія Іванівна https://orcid.org/0000-0001-9500-9224
Keywords: Zemstvo veterinary medicine; земська ветеринарна медицина; non-infectious pathology of productive animals; незаразна патологія продуктивних тварин; innovations in veterinary equipment; розвиток ветеринарних технологій; veterinary culture in Ukraine; ветеринарна культура в Україні